Assessment of Pangasinan Language Resources: A Document Review - Razo, Shalyra; Cauan, Mia Hazel; Abrigo, Kate Marsie; Gabino, Edraliz; Pelila, John Rey (Journal of Multidisciplinary Research and Development, 2026)
This study assessed the availability of resources that support the teaching and learning of the Pangasinan language, one of the eight major languages in the Philippines. Focusing on materials that aid instruction and promote language preservation, a document review was conducted in a public library in Northern Luzon. A total of 57 materials were identified and classified by form, publication year, authorship, language, and publication status. Findings reveal a steady increase in Pangasinan language writings since 1889, mostly authored by local writers. Many materials combine Pangasinan with English or Filipino and vary in publication status. These resources primarily cover literature, language background, and linguistics. However, the study highlights a significant lack of core linguistic resources, such as dictionaries and grammar books, which are essential for effective language instruction. This gap hinders both the teaching process and the implementation of mother tongue-based multilingual education. It is concluded that while valuable materials exist, they remain insufficient for comprehensive instruction. Therefore, increased production and accessibility of linguistic resources are urgently needed. Collaboration with higher education institutions is recommended to develop and integrate these materials into formal instruction. These efforts are vital not only for improved educational outcomes but also for the preservation and revitalization of the Pangasinan language.